Instrumentation for the environmental assessment of the built environment of rural settlements - Hernández, H (Nexo Revista Científica, 2010)
The instrumental contains a system of indicators obtained from a study based on relevant concepts and criteria as well as the characterization of rural settlements. The system of indicators includes parameters which evaluate the environmental factors that constitute the rural settlement. The instrumental design has an implicit systemic and integral focus in order to achieve local sustainability. The instrument has been validated in five rural settlements within the municipality of Masaya, Nicaragua. The system of indicators was obtained from a compilation of the most significant forty variables or components. Taking into account the Theory of Systems and using a process of association, significance and graphical interrelationships fifteen specific indicators were obtained as well as six general indicators with their corresponding system category. The results of the validation are shown using histograms and matrices. In conclusion, the instrumental allows measurement and assessment of the environmental quality of settlements. It also demonstrates limitations as well as potential for improvement in living conditions for residents. The instrument can also act as a guide for integral development within rural settlements as well as the wider regions. Keywords: environmental quality; indicators; rural settlements; environmental assessment. DOI: 10.5377/nexo.v22i1.38 Nexo: Revista Científica Vol.22, No.01, pp.02-09/Agosto 2009